2018
DOI: 10.1186/s13058-018-0975-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying an early treatment window for predicting breast cancer response to neoadjuvant chemotherapy using immunohistopathology and hemoglobin parameters

Abstract: BackgroundBreast cancer pathologic complete response (pCR) to neoadjuvant chemotherapy (NAC) varies with tumor subtype. The purpose of this study was to identify an early treatment window for predicting pCR based on tumor subtype, pretreatment total hemoglobin (tHb) level, and early changes in tHb following NAC.MethodsTwenty-two patients (mean age 56 years, range 34–74 years) were assessed using a near-infrared imager coupled with an Ultrasound system prior to treatment, 7 days after the first treatment, at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 46 publications
(50 reference statements)
0
37
0
Order By: Relevance
“…Diffuse optical tomography and diffuse optical spectroscopy exploit changes in tumor vascularity and metabolism and have demonstrated the potential for early prediction of breast cancer pathological response (18)(19)(20)(21)(22)(23)(24)(25)(26). Studies have shown accurate predictions in the neoadjuvant setting by utilizing pretreatment hemoglobin levels and changes in hemoglobin early in the course of treatment (19,(21)(22)(23)(24)(25)(26), or by monitoring changes of blood oxygen saturation sO2 at day 1 of dose dense treatment (18) or day 10 during early treatment (20). In the recent ACRIN 6691 trial evaluating 36 patients, the authors derived a tissue optical index (TOI), a product of deoxygenated Hb and water concentration over lipid, and reported that the mid-treatment TOI can predict pCR with AUC 0.6 to 0.83 (19).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Diffuse optical tomography and diffuse optical spectroscopy exploit changes in tumor vascularity and metabolism and have demonstrated the potential for early prediction of breast cancer pathological response (18)(19)(20)(21)(22)(23)(24)(25)(26). Studies have shown accurate predictions in the neoadjuvant setting by utilizing pretreatment hemoglobin levels and changes in hemoglobin early in the course of treatment (19,(21)(22)(23)(24)(25)(26), or by monitoring changes of blood oxygen saturation sO2 at day 1 of dose dense treatment (18) or day 10 during early treatment (20). In the recent ACRIN 6691 trial evaluating 36 patients, the authors derived a tissue optical index (TOI), a product of deoxygenated Hb and water concentration over lipid, and reported that the mid-treatment TOI can predict pCR with AUC 0.6 to 0.83 (19).…”
Section: Resultsmentioning
confidence: 99%
“…In Appendix A, we developed treatment prediction models using combined data from 38 patients reported in this study and 22 patients acquired in an earlier study with similar DOT system parameters, patient and treatment characteristics (19). Table 1 summarizes patient and tumor characteristics, NAT regimens and MP grading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DOSI measures absolute concentrations of oxyhemoglobin, deoxyhemoglobin, lipid, and water. These parameters have been shown by multiple research groups to be valuable prognostic markers at various points throughout NAC [6,9,16,21,27,45,46,48,49,50,53]. For example, a recent landmark multicenter study (ACRIN 6691) showed that changes in tumor deoxyhemoglobin, water, and lipid at midpoint of NAC correlated strongly to pCR [48].…”
Section: Introductionmentioning
confidence: 99%